Frequency of Sensorineural Hearing Loss in Chronic Otitis Media - Abdul Shakoor, Ameer Humza, Hassan Majid Bhatti, Mohammad Qamar Nasir, Ruqqiya Saadat, Syed Umair Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To estimate the frequency of sensorineural hearing loss in chronic otitis media. Study design: Descriptive study. Place and duration of study: Department of ENT, Services Hospital Lahore from 1st June 2021 to 30th November 2021. Methodology: One hundred patients diagnosed with chronic otitis media were enrolled. Their clinical details were documented and audiograms were performed. Frequency of sensorineural hearing loss was determined. Results: Mean age of 27.9±6.1 years with 59% males and 41% females. There were 52% patients who were diagnosed with the sensorineural hearing loss while it was not present in the 48% of the patients whereas significant difference within the positive patients with sensorineural hearing loss and longer duration of infection was observed in comparison to sensorineural hearing loss negative cases. Conclusion: A high frequency of sensorineural hearing loss is presented in chronic otitis media cases. Keywords: Frequency, Sensorineural hearing loss, Chronic otitis media